2015
DOI: 10.1002/biot.201400393
|View full text |Cite
|
Sign up to set email alerts
|

Emerging influenza viruses and the prospect of a universal influenza virus vaccine

Abstract: Influenza viruses cause annual seasonal epidemics and pandemics at irregular intervals. Several cases of human infections with avian and swine influenza viruses have been detected recently, warranting enhanced surveillance and the development of more effective countermeasures to address the pandemic potential of these viruses. The most effective countermeasure against influenza virus infection is the use of prophylactic vaccines. However, vaccines that are currently in use for seasonal influenza viruses have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 137 publications
(155 reference statements)
0
58
0
Order By: Relevance
“…If predictions are wrong and the vaccine and the circulating strains are mismatched, vaccine efficacy drops significantly [2]. In addition pandemics occur at irregular intervals and seasonal vaccines are ineffective against those novel viruses [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…If predictions are wrong and the vaccine and the circulating strains are mismatched, vaccine efficacy drops significantly [2]. In addition pandemics occur at irregular intervals and seasonal vaccines are ineffective against those novel viruses [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Three human cases of H10N8 virus have been reported in China so far, two of which were fatal (1)(2)(3). Furthermore, an avian H10N7 strain was found to be the etiological agent responsible for the massive die-off harbor seals in the Baltic Sea, an epidemic that killed more than 10% of the local seal population (4)(5)(6).…”
mentioning
confidence: 99%
“…We found that memory CD4 T cells specific for H5 HA persisted in subjects vaccinated many years earlier and that these could be recruited into a subsequent immune response to vaccination, enabling a greatly enhanced antibody response to a serologically distinct H5N1-derived virus (20). Should avian influenza viruses continue to pose a threat to humans (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), such a prepandemic strategy could enhance vaccine responsiveness in "at risk" subjects and enhance early and potentially protective antibody responses in infected individuals.…”
Section: Discussionmentioning
confidence: 93%